2006
DOI: 10.1038/sj.bjp.0706836
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin inhibits inflammatory hypernociception

Abstract: Background and purpose: Atorvastatin is an inhibitor of the enzyme 3-hydroxyl-3-methylglutaryl coenzyme A reductase used to prevent coronary heart disease. We have studied the analgesic effect of atorvastatin in inflammatory models in which a sequential release of mediators (bradykinin, (BK), tumour necrosis factor-a (TNF-a), interleukin-1b (IL-1b) and the chemokine, KC/CXCL) links the stimulus with release of directly acting hypernociceptive mediators such as prostaglandin E 2 (PGE 2 ). Experimental approach:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
52
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 74 publications
2
52
0
Order By: Relevance
“…Oxaliplatin modulates the activity of ionic channels, particularly voltagegated sodium channels (37,38). A previous study using hippocampal slices has shown that neurotransmission sensitization induced by theta burst stimulation (10 bursts of 4 pulses at 100 Hz with 200ms interburst intervals) induces phosphoryla tion of cofilin (39). Therefore, the increase of cofilin phosphorylation in the spinal cord induced by oxaliplatin might be caused by sensory nerve activation.…”
Section: Discussionmentioning
confidence: 99%
“…Oxaliplatin modulates the activity of ionic channels, particularly voltagegated sodium channels (37,38). A previous study using hippocampal slices has shown that neurotransmission sensitization induced by theta burst stimulation (10 bursts of 4 pulses at 100 Hz with 200ms interburst intervals) induces phosphoryla tion of cofilin (39). Therefore, the increase of cofilin phosphorylation in the spinal cord induced by oxaliplatin might be caused by sensory nerve activation.…”
Section: Discussionmentioning
confidence: 99%
“…These carrageenan-activated inflammatory cascades are related not only to the innate immunity but also to the generation of reactive oxygen species (ROS) (34). Since inflammation is closely linked to the production of ROS, the molecular basis of the observed anti-inflammatory effects of statins may be related to their ability to block the production and/or activity of ROS (35). Therefore, the results of the present study indicate an anti-inflammatory effect of lovastatin on the paw edema and leukocyte migration in peritoneal exudate induced by carrageenan, inhibition of MPO release from in vitro human neutrophils, and an anti-nociceptive action in the formalin test.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory hypemociceptive mediators, such as prostaglandins (PGs), considered to be directly acting on their specific metabotropic receptors present on the primary sensory neurons (33). PGE2, a pro-inflammatory prostanoid, exerts its effect by acting via PGE receptor subtypes, EPI to EP4 (34).…”
Section: Discussionmentioning
confidence: 99%